Study on Crystallization Behaviors and Properties of F-III Fibers during Hot Drawing in Supercritical Carbon Dioxide - Ding, Xiaoma (Polymers (Basel), 2019)
In order to obtain F-III fibers with high mechanical properties, pristine F-III fibers were hot drawn at the temperature of 250 °C, pressure of 14 MPa, tension of 6 g·d(−1), and different times, which were 15 min, 30 min, 45 min, 60 min, 75 min, 90 min, and 105 min, respectively, in supercritical carbon dioxide (Sc-CO(2)) in this article. All the samples, including the pristine and treated F-III fibers, were characterized by a mechanical performance tester, wide-angle X-ray scattering (WAXS), small-angle X-ray scattering (SAXS), and thermogravimetric analysis (TGA). The results showed that the thermal stability of F-III fibers was enhanced to some extent, and the tensile strength and modulus of F-III fibers had great changes as the extension of treatment time during hot drawing in Sc-CO(2), although the treatment temperature was lower than the glass transition temperature (Tg) of F-III fibers. Accordingly, the phase fraction, orientation factor f(c) of the (110) crystal plane, fibril length l(f), and misorientation angle B(φ) of all the samples were also investigated. Fortunately, the hot drawing in Sc-CO(2) was successfully applied to the preparation of F-III fibers with high mechanical properties.